A Novel and Validated Inflammation-Based Score (IBS) Predicts Survival in Patients With Hepatocellular Carcinoma Following Curative Surgical Resection: A STROBE-Compliant Article. Issue 7 (February 2016) - Fu, Yi-Peng; Ni, Xiao-Chun; Yi, Yong; Cai, Xiao-Yan; He, Hong-Wei; Wang, Jia-Xing; Lu, Zhu-Feng; Han, Xu; Cao, Ya; Zhou, Jian; Fan, Jia; Qiu, Shuang-Jian
Abstract : Abstract: As chronic inflammation is involved in the pathogenesis and progression of hepatocellular carcinoma (HCC), we investigated the prognostic accuracy of a cluster of inflammatory scores, including the Glasgow Prognostic Score, modified Glasgow Prognostic Score, platelet to lymphocyte ratio, Prognostic Nutritional Index, Prognostic Index, and a novel Inflammation-Based Score (IBS) integrated preoperative and postoperative neutrophil to lymphocyte ratio in 2 independent cohorts. Further, we aimed to formulate an effective prognostic nomogram for HCC after hepatectomy. Prognostic value of inflammatory scores and Barcelona Clinic Liver Cancer (BCLC) stage were studied in a training cohort of 772 patients with HCC underwent hepatectomy. Independent predictors of survival identified in multivariate analysis were validated in an independent set of 349 patients with an overall similar clinical feature. In both training and validation cohorts, IBS, microscopic vascular invasion, and BCLC stage emerged as independent factors of overall survival (OS) and recurrence-free survival (RFS). The predictive capacity of the IBS in both OS and RFS appeared superior to that of the other inflammatory scores in terms of C-index. Additionally, the formulated nomogram comprised IBS resulted in more accurate prognostic prediction compared with BCLC stage alone. IBS is a novel and validated prognostic indicator of HCC after curative resection, and a robust HCC nomogram including IBS was developed to predict survival for patients after hepatectomy. Abstract : Supplemental Digital Content is available in the text